(untitled) (The International Journal of Educational Sciences and Arts, 2023)
Relying on mobile applications to manage academic and educational advising processes has an effective role in improving the advising environment in higher education institutions. The emergence of gamification as a technology that can be integrated into many digital applications has led to a reconsideration of how applications are designed so that they are more capable and effective in enhancing user engagement in these applications. Accordingly, the current research examines the effect of using a gamification-based academic advising application in improving engagement with advising tasks among higher education students. The quasi-experimental approach was used to compare the first experimental group that used the academic advising application and the second experimental group that used the same application without activating the gamification system. The research sample consisted of (60) female students who were randomly distributed into the two research groups. A measure of engagement in instructional tasks was developed, consisting of three axes: behavioral engagement, cognitive engagement, and emotional engagement, with a total of (24) items. The results showed the advantage of the first experimental group that used the gamification-based academic advising application in improving indicators of engagement in advising tasks. The research recommended the need to expand the use of gamification in academic advising environments to improve the advising environment in higher education institutions. The research also recommended the need to train faculty members to use gamification incentives in managing academic advising processes.